Solutions to improve the quality of public asset management at PetroViet Nam Power Ca Mau Company - Đặng, Thị Thủy Tranh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
The study focuses on analyzing and evaluating the current state of public asset management in typical state-owned enterprises managing public assets at Ca Mau Power Company in the period of 2019-2021. Improving the quality of management stemming from transparency, transparency from actual needs, transparency from procurement, transparency in management, transparency in use will be the premise to improve the quality of financial management. produce. On the basis of analyzing the actual situation at Ca Mau Petro Vietnam Power Company from the achievements and limitations, the author proposes solutions to improve the quality of public asset management: Building a management version; Applying information technology to the field of management; Training and guidance; Strengthen inventory management; Group of solutions to improve the efficiency of using short-term assets; Group of solutions to improve the efficiency of long-term asset use; Management solutions according to the efficiency of asset use thr